Lesinurad monotherapy in gout patients intolerant to a xanthine oxidase inhibitor: a 6 month phase 3 clinical trial and extension study. (23rd September 2017) - Tausche, Anne-Kathrin; Alten, Rieke; Dalbeth, Nicola; Kopicko, Jeff; Fung, Maple; Adler, Scott; Bhakta, Nihar; Storgard, Chris; Baumgartner, Scott; Saag, Kenneth
Abstract: Objective: To investigate the efficacy and safety of lesinurad, a selective uric acid reabsorption inhibitor, in a 6 month, phase 3 clinical trial and extension study. Methods: Patients with gout who cannot take a xanthine oxidase inhibitor (XOI) and have serum uric acid (sUA) ⩾6.5 mg/dl were randomized to receive oral lesinurad (400 mg daily) or placebo. The primary endpoint was the proportion of patients with sUA <6.0 mg/dl at month 6. Safety assessments included treatment-emergent adverse events (TEAEs) and laboratory data. Patients who completed the study were eligible for an open-label, uncontrolled extension study of lesinurad 400 mg monotherapy. Results: Patients ( n = 214) were primarily white males (mean age 54.4 years; gout duration 11.2 years). Significantly more patients achieved the primary endpoint with lesinurad than placebo (29.9 vs 1.9%; P < 0.0001). Overall TEAE rates were higher with lesinurad (77.6 vs 65.4%); renal-related TEAEs (17.8%), renal-related serious TEAEs (4.7%) and serum creatinine elevations (1.5 times baseline, 24.3%) occurred only with lesinurad. A total of 143 patients (65 lesinurad, 78 placebo) enrolled in the extension study. Treatment with lesinurad 400 mg resulted in rapid and sustained sUA lowering that persisted for up to 18 months before the study was terminated prematurely. No new safety findings were observed in the extension. Conclusion: In patients with gout and intolerance/contraindication to XOIs, lesinurad 400 mg monotherapy demonstrated superior sUA lowering compared with placebo, with sustained effects for up to 18 months. Due to a high incidence of serum creatinine elevations and renal-related adverse events, including serious adverse events with lesinurad 400 mg, lesinurad should not be used as monotherapy. Trial registration: ClinicalTrials.gov (http://clinincaltrials.gov ), NCT01508702